Endovascular treatment of intracranial microarteriovenous malformations. - Andreou, A; Ioannidis, I; Lalloo, S; Nickolaos, N; Byrne, J (2008)
OBJECT: Microarteriovenous malformations (micro-AVMs) are an uncommon subgroup of brain AVMs defined by a nidus measuring < 1 cm in diameter. The clinical features, angiographic characteristics, and outcomes in patients with micro-AVMs who had been treated endovascularly after presenting with hemorrhage were reviewed to identify common features affecting prognosis. METHODS: Between 1997 and 2006, 25 patients (12 females and 13 males) with 26 micro-AVMs were treated. Twenty-four patients presented with intracerebral hematoma and 1 with subarachnoid hemorrhage only. All patients underwent CT on admission, diagnostic cerebral angiography, and 1 session of endovascular treatment during the acute phase. RESULTS: Procedure-related complications occurred in 3 patients (12%), which caused temporary hemiparesis in 1 (4%) and no clinical sequelae in 2 patients (8%). Complete nidus obliteration was achieved at the end of the embolization in 22 (84.6%) of 26 lesions. Two recurrences were evident on follow-up angiography 6 months postembolization, resulting in a complete obliteration rate of 77% (20 of 26 lesions) after a single treatment. Late angiography was performed in 12 patients, and no further recurrences were identified. CONCLUSIONS: Immediate complete obliteration of a micro-AVM with a high permanent cure and low morbidity rates was accomplished using endovascular treatment. Early embolization after bleeding should be considered as an alternative to resection.